A shift toward inhibitory receptors and impaired effector functions on NK cells contribute to immunosuppression during sepsis. Issue 1 (6th August 2019) - Feng, Ting; Liao, Xuelian; Yang, Xuewei; Yang, Chuan; Lin, Fang; Guo, Yinkun; Kang, Yan; Li, Hong
Abstract: Most information about the immune status of NK cells during sepsis has been obtained from animal models, athough data from clinical septic patients is limited. In this study, we aimed to decipher NK cell immunity of septic patients in a more comprehensive way. We found that cytotoxicity of NK cells dramatically decreased during sepsis, likely due to the reduction of cluster of differentiation (CD)3 − CD56 + NK cells and a shift of phenotypic changes of NK group 2 member (NKG2) receptors, natural cytotoxicity receptors (NCRs) and killer immunoglobulin-like receptors (KIRs) toward inhibitory receptors demonstrated by CD3 − CD56 + NK cells in septic patients. Expression of the activation indicator CD69 and cytotoxic associated marker CD107a on CD3 − CD56 + NK cells in healthy adults was significantly lower than that of septic patients. Although perforin and granzyme B on CD3 − CD56 + NK cells from all groups exhibited equivalently high levels, CD3 − CD56 + NK cells from septic patients exhibited a much lower fold increase of CD69 and CD107a compared with healthy adults after coculturing with K562 cells in vitro . Cytokine production of IFN-γ and TNF-α on CD3 − CD56 + NK cells in septic patients was also impaired after stimulation by PMA and ionomycin. We found that the proportion of NK cells in lymphocytes was negatively associated with patient 28 d death in septic patients. Phenotypic changes of a shift toward inhibitory receptors and impairment of effector functions of NK cells might be an important mechanism of immunosuppression during sepsis.